Moody Oil - What is Driving the Crude Oil Price? - Filippo Lechthaler; Lisa Leinert (ETH Zurich, CER-ETH - Center of Economic Research, 2012)
The unparalleled surge of the crude oil price after 2003 has triggered a heated scientific and public debate about its ultimate causes. Unexpected demand growth particularly from emerging economies appears to be the most prominently supported reason among academics. We study the price dynamics after 2003 in the global crude oil market using a structural VAR model. We account for structural breaks and approximate market expectations using a time series for media sentiment in order to contribute to the existing literature. We and that forward-looking demand activities rather than demand arising from current needs have played an important role for the run-up in the price of crude oil after 2003. We additionally and that emerging economies have not majorly contributed to the price surge
Keywords: Q43; Q41; C32; D8; E3; 330; Oil Price; Spot Market; Futures Market; Fundamentals; Speculation; Financialization; Ölpreis; Rohstoffderivat; Volatilität; Spotmarkt; Finanzanalyse; VAR-Modell